O papel da família na garantia do direito à aprendizagem das crianças da educação infantil durante o ensino remoto em período pandêmico : um estudo a partir do programa rádio escola em Benjamin Constant - AM - Souza, Janaina Silva de (Brasil, 2023)
This Course Completion work is a scientific production that aimed to analyze the role of the family during remote teaching in a pandemic period via the Escola Radio Program-PRE- to continue guaranteeing the right to learning of children in kindergarten from the Francisco Chagas de Almeida Municipal School. To achieve this end, we sought to describe the organization and development of remote classes for early childhood education, via the radio school-PRE program; learn how the family contributed to the learning and development of children during remote teaching via the school radio program; and identify the difficulties faced and the factors that facilitated families during remote teaching to accompany children in classes via PRE and contribute to their learning and development. The study presented a description of the educational actions of the PRE for early childhood education and the contribution of the family in the educational process of children in remote teaching during the pandemic, through the PRE, emphasizing the ways in which they contributed to the learning of children . The research showed that the mothers involved in the study organized the time, space and materials for the children's classes, as well as reinforcing the knowledge and actions worked on by the teachers over the radio, supporting the children to respond to the handouts, interact with the teachers from the radio during remote classes and with the teacher of their child's class when they picked up or took the handouts to school, as well as promoted actions and moments of coexistence that promoted the child's right to learning and development.